Analysis of Distance Learning During Covid-19 Pandemic in Indonesia - Zaharah Zaharah (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The purpose of this study is to analyze the impact of distance learning during the Covid-19 pandemic, where the teaching and learning process is usually carried out in the classroom but with the pandemic, learning must be done remotely or through online learning. The method used in this research is descriptive quantitative. 40 students and 10 prospective teachers practice teaching in junior and senior high schools as respondents in South Tangerang. The data was collected using Google forms and the results were analyzed statistically discritif. This research was conducted at the Tarbiyah Faculty, Syarif Hidayatullah State Islamic University Jakarta and several schools in South Tangerang. The results obtained were around 55.5% of students experienced an increase in understanding in learning, only 47.5% of students paid less attention to lessons when learning online and 59.5% of students could concentrate on following online learning, almost 60% of students preferred to study offline. than online. This is because some students have difficulty participating in distance learning because they are constrained by unstable internet connections and lack of funds to purchase internet quotas, and teachers lack expertise in learning technology, especially in using learning applications, so learning does not run smoothly. Based on the analysis of respondents' results, it can be concluded that distance learning carried out during the pandemic is effective, but in particular only during the pandemic because of the many obstacles experienced by students and teachers. However, when it returns to normal, you should not continue to use online learning, but must have done face-to-face learning or blended learning so that students do not experience boredom in participating in learning.Keywords: Learning; Covid-19; Face to face AbstrakTujuan dari penelitian ini adalah untuk menganalisis dampak pembelajaran jarak jauh pada masa pandemi Covid-19, dimana proses belajar mengajar biasanya dilakukan di dalam kelas namun dengan adanya pandemi, pembelajaran harus dilakukan dari jarak jauh atau melalui pembelajaran online. Metode yang digunakan dalam penelitian ini adalah deskriptif kuantitatif. 40 Mahasiswa dan 10 calon guru praktik mengajar di SMP dan SMA sebagai responden yang ada di Tangerang Selatan. Data dikumpulkan menggunakan Google form dan hasilnya dianalisis secara statistik diskriftif. Penelitian ini dilakukan di Fakultas Tarbiyah, Universitas Islam Negeri Syarif hidayatullah Jakarta dan beberapa sekolah yang ada di Tangerang Selatan. Hasil yang diperoleh sekitar 55,5% siswa mengalami peningkatan pemahaman dalam pembelajaran, hanya 47,5% peserta didik kurang memperhatikan pelajaran ketika pelajaran online dan 59,5% siswa dapat konsentrasi dalam mengikuti pembelajaran online, hampir 60% siswa lebih suka belajar secara offline daripada online. Hal ini disebabkan sebagian siswa mengalami kesulitan mengikuti pembelajaran jarak jauh karena terkendala oleh koneksi internet tidak stabil dan kekurangan dana untuk membeli kuota internet, serta guru kurang memiliki keahlian dalam teknologi pembelajaran terutama dalam menggunakan aplikasi pembelajaran, sehingga pembelajaran tidak berjalan dengan lancar. Berdasarkan analisis hasil responden dapat disimpulkan, bahwa pembelajaran jarak jauh yang dilakukan selama masa pandemi efektif, tetapi khususnya hanya masa pandemic saja karena banyaknya kendala yang dialami siswa dan guru. Namun saat sudah kembali normal, sebaiknya tidak terus menerus mengunakan pembelajaran online, tetapi harus sudah melakukan pembelajaran tatap muka ataupun blended learning agar peserta didik tidak mengalami kebosanan dalam mengikuti pembelajaran.Kata Kunci: Pembelajaran; Covid-19; Tatap Muka